2007
DOI: 10.1093/jxb/erm255
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci for flowering time and morphological traits in multiple populations of Brassica rapa

Abstract: Wide variation for morphological traits exists in Brassica rapa and the genetic basis of this morphological variation is largely unknown. Here is a report on quantitative trait loci (QTL) analysis of flowering time, seed and pod traits, growth-related traits, leaf morphology, and turnip formation in B. rapa using multiple populations. The populations resulted from crosses between the following accessions: Rapid cycling, Chinese cabbage, Yellow sarson, Pak choi, and a Japanese vegetable turnip variety. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
134
1
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 141 publications
(158 citation statements)
references
References 30 publications
17
134
1
4
Order By: Relevance
“…This indicates genotype 3 environment 3 developmental stage effects on leaf development. Several other studies also showed the impact of diverse environments on QTL detection for leaf development in Brassica species and maize (Zea mays; Lou et al, 2007;Li et al, 2009;Ku et al, 2012;Raman et al, 2013). Temporal analysis of leaf growth showed both different and common pQTLs at different growth stages, which accumulated to a large number of loci affecting leaf development ( Fig.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…This indicates genotype 3 environment 3 developmental stage effects on leaf development. Several other studies also showed the impact of diverse environments on QTL detection for leaf development in Brassica species and maize (Zea mays; Lou et al, 2007;Li et al, 2009;Ku et al, 2012;Raman et al, 2013). Temporal analysis of leaf growth showed both different and common pQTLs at different growth stages, which accumulated to a large number of loci affecting leaf development ( Fig.…”
Section: Discussionmentioning
confidence: 78%
“…The genetic regulation of leaf architecture has been unraveled through quantitative trait locus (QTL) analyses in Brassica species (Lou et al, 2007;Kubo et al, 2010;Yu et al, 2013). Lan and Paterson (2001) located significant QTLs explaining 45% of the phenotypic variation in lamina length (LL), three of which colocalized with QTLs that affected leaf width (LW) in B. oleracea.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore the syntenic relationship with the related genus Arabidopsis is now well established (reviewed by Schranz et al 2006) and allows the comparison of map positions between Brassica and Arabidopsis. For B. rapa QTL analyses have been described for a wide variety of morphological and physiological traits such as seed colour, pubescence, flowering time (Teutonico and Osborn 1994;Song et al 1995;Nozaki et al 1997;Lou et al 2007), oleic acid concentration (Tanhuanpaa et al 1996), linolenic acid content (Tanhuanpaa and Schulman 2002), clubroot resistance (Suwabe et al 2006) and black rot resistance (Sogengas et al 2007). As microspore culture can be applied efficiently in Brassica species, doubled haploid (DH) populations are presently the preferred mapping populations for QTL studies because of their immortality and homozygosity which allows replicated experiments.…”
Section: Introductionmentioning
confidence: 99%
“…As already stated, altered expression of AtCOL1 in transgenic plants did not affect flowering time (Ledger et al 2001). In other Brassica species such as B. oleracea, B. rapa, and B. napus, QTL studies have suggested genes other than COL1 to be the most important for flowering time variation in these species (Schranz et al 2002;Kim et al 2006;Okazaki et al 2007;Lou et al 2007). Of course, this does not rule out the involvement of AtCOL1 in other, yet undetected, functions, and the possibility that the lack of evidence on the involvement of COL1 in the control of flowering time is simply reflecting a lack of power of the QTL studies carried out in other Brassica species.…”
Section: Evidence Of Selection On Col1mentioning
confidence: 82%